2016
DOI: 10.1089/pho.2015.3960
|View full text |Cite
|
Sign up to set email alerts
|

The Bactericidal Effect of 2780 and 940 nm Laser Irradiation onEnterococcus faecalisin Bovine Root Dentin Slices of Different Thicknesses

Abstract: The results of this in vitro study showed that the dual wavelength laser system obtained a significantly higher bactericidal effect on E. faecalis than Er,Cr:YSGG laser, reaching a depth of 1000 μm of dentin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 36 publications
2
12
0
4
Order By: Relevance
“…Therefore, it is recommended that similar studies be carried out in curved root canals, too, to make it possible to extend the results to real clinical conditions. Furthermore, in previous studies, application of lasers, photodynamic therapy and agitation of the irrigation solution with ultrasonic devices have drawn attention as antimicrobial adjuncts and it has been reported that they increase penetration of irrigation solutions into more apical areas and root canal irregularities (20,28). It is suggested that the efficacy of these procedures in association with NaOCl, as the most effective canal irrigation solution, be evaluated in relation to old and mature biofilms and mixed bacterial species of the root canal system so that the best antimicrobial protocol can be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is recommended that similar studies be carried out in curved root canals, too, to make it possible to extend the results to real clinical conditions. Furthermore, in previous studies, application of lasers, photodynamic therapy and agitation of the irrigation solution with ultrasonic devices have drawn attention as antimicrobial adjuncts and it has been reported that they increase penetration of irrigation solutions into more apical areas and root canal irregularities (20,28). It is suggested that the efficacy of these procedures in association with NaOCl, as the most effective canal irrigation solution, be evaluated in relation to old and mature biofilms and mixed bacterial species of the root canal system so that the best antimicrobial protocol can be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the conventional method, lasers of suitable wavelengths have an excellent capacity for bacterial reduction at elimination depths exceeding 1000 μm in deep dentin tubules [13,21,22]. However, despite the potential benefits of lasers, too high, a dose of the absorbed energy may cause thermal damage to periodontal ligaments and lad to bone necrosis [15,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Endodontia tem evoluído com objetivo de promover a desinfecção do sistema de canais radiculares (Hmud, Kahler et al, 2010;Asnaashari e Safavi, 2013;Gutknecht, Al-Karadaghi et al, 2016). O laser diodo em diferentes comprimentos de onda (970nm e 808nm) foi desenvolvido para aplicação em Endodontia, apresentando fibras ópticas finas, com 200-320 µm de diâmetro, que permitem adaptação às dimensões reduzidas e curvaturas dos canais radiculares, possibilitando a descontaminação ao longo do conduto (Brugnera, Zanin et al, 2003), bem como a ação do laser no terço apical do canal radicular (Beer, Buchmair et al, 2012;Maenosono, Bim Junior et al, 2015;Lopes, Roperto et al, 2016).…”
Section: Dentro Desse Contexto O Potencial De Aplicação Do Laser No unclassified
“…Com a finalidade de promover a descontaminação efetiva do SCR, terapias alternativas e coadjuvantes ao tratamento endodôntico foram propostas, como o uso de diferentes tipos de lasers (HMUD et al, 2010;ASNAASHARI et al, 2013;GOMES et al, 2013;ARNEIRO et al, 2014;LLENA et al, 2015;GUTKNECHT et al, 2016;MORAGO et al, 2016), entre eles o laser diodo, que ao atuar em camadas mais profundas da dentina (ALFREDO et al, 2009), permite a redução dos microrganismos no interior do SCR (SCHOOP et al, 2006;KANUMURU et al, 2014;MASHALKAR et al, 2014;ASNAASHARI et al, 2016).…”
Section: Análise Estatísticaunclassified
See 1 more Smart Citation